The impact of the composition of the crude oils on the wax crystallization - Hosseinipour, A. (Trans Tech Publications Ltd, 2014)
One of the major problems in petroleum industry is wax precipitation and deposition. The componentâs compositional and structural analysis of the crude oils is key factors to be studied to mitigate wax formation and precipitation tendency for the betterment of the crude oil flowability. In this work, the compositions and structures of two Malaysian and Sudanese crude oil samples were determined to investigate their effects on wax precipitation. The GC/MS was used to analyze hydrocarbon components. For this work, high pressure micro differential scanning calorimetry (HPÎ¼DSC) is used to determine the wax crystallization point and solubility curve. Results showed a linear relationship between wax appearance temperature (WAT) and weight percentage of component in the crude oil having > 14 carbon atoms. In addition, the effect of temperature on the amount of wax precipitation has also been investigated. Â© 2014 Trans Tech Publications, Switzerland.